Republic of Armenia : 2008 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Armenia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2008 Article IV Consultation highlights that Armenia's recent economic performance has remained strong, and the economy is poised for another year of double-digit growth. Rising inflation, a widening current account deficit, and rapid credit growth have raised concerns about overheating. Executive Directors have commended the authorities for the successful implementation of macroeconomic policies under the Poverty Reduction and Growth Facility (PRGF)-supported program that expired in May 2008. Directors have also welcomed the authorities' intention to withdraw fiscal stimulus during 2008-09 to address current imbalances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet